The Stereochemical Basis of the Genetic Code and the (Mostly) Autotrophic Origin of Life - Fontecilla-Camps, Juan C. (Life (Basel), 2014)
Spark-tube experiments and analysis of meteorite contents have led to the widespread notion that abiotic organic molecules were the first life components. However, there is a contradiction between the abundance of simple molecules, such as the amino acids glycine and alanine, observed in these studies, and the minimal functional complexity that even the least sophisticated living system should require. I will argue that although simple abiotic molecules must have primed proto-metabolic pathways, only Darwinian evolving systems could have generated life. This condition may have been initially fulfilled by both replicating RNAs and autocatalytic reaction chains, such as the reductive citric acid cycle. The interactions between nucleotides and biotic amino acids, which conferred new functionalities to the former, also resulted in the progressive stereochemical recognition of the latter by cognate anticodons. At this point only large enough amino acids would be recognized by the primordial RNA adaptors and could polymerize forming the first peptides. The gene duplication of RNA adaptors was a crucial event. By removing one of the anticodons from the acceptor stem the new RNA adaptor liberated itself from the stereochemical constraint and could be acylated by smaller amino acids. The emergence of messenger RNA and codon capture followed.